Comparative Analysis of BGP, OSPF, and RIP Dynamic Routing Protocols in Metro Ethernet Network and Broadband Service Implementation - Ekie Revsie Akbar; Try Mulyoto; Imelda Imelda (International Journal Software Engineering and Computer Science (IJSECS), 2026)
The reliability of Internet Service Provider (ISP) networks increasingly depends on the routing protocols employed to manage traffic across distributed infrastructure. This study investigates and compares the operational performance of three widely adopted dynamic routing protocols — Border Gateway Protocol (BGP), Open Shortest Path First (OSPF), and Routing Information Protocol (RIP) — deployed across the Metro Ethernet network of PT Kreatif Data Prima Nusantara, a regional ISP located in Kedaton, Bandar Lampung, Indonesia. The existing network architecture relies on a combined deployment of static routing and OSPF distributed across four Points of Presence (POP): QNN, Tamin, Labuhan Dalam, and INQI. This hybrid configuration has repeatedly produced prolonged convergence delays, operational complexity in fault isolation, and constrained scalability. A simulation-based experimental methodology was adopted, replicating the physical network topology using MikroTik RouterOS-based Cloud Core Routers (CCR). Key performance indicators evaluated include convergence time, CPU utilization, bandwidth overhead, and overall network availability. Experimental outcomes clearly show BGP's superior performance: an average convergence time of 18.36 seconds — substantially faster than RIP's 28.34 seconds and more resource-efficient across all measured dimensions, despite OSPF's faster raw reconvergence at 3.21 seconds; CPU utilization of only 11% compared to 19% for OSPF and 38% for RIP; and bandwidth overhead of 1.9 Kbps versus 9.2 Kbps for OSPF and 26.8 Kbps for RIP. BGP also recorded the highest network availability at 99.98%. The simulation topology encompasses four POPs — a relatively small-scale environment — and results should be read within that scope. These findings support the recommendation that PT Kreatif Data Prima Nusantara adopt a full BGP deployment as its primary routing strategy to improve long-term operational efficiency, network manageability, and service reliability.